Models of Innovation Development: Measurement Indicators and their Interaction (a Case Study of Kazakhstan) - BISHIMBAYEVA, Saule Kozykeyevna; NURASHEVA, Kulyanda Kulbosynovna; NURMUKHANBETOVA, Aigul Adilzhanovna (Journal of Advanced Research in Law and Economics, 2018)
The goal of the study is to demonstrate that the Triple Helix model neither sufficiently reflects the process of innovation development nor justifies the fourth helix, the indicators of which describe the real situation in the social and economic area of the country and are an important element of the innovation ecosystem. The study uses empirical methods: observation, measurement, description of facts; logical inferences; sampling of the required information, its grouping; system and statistical analysis; and comparison of the indicators under study. The analysis of the existing models of innovation development and their applicability in Kazakhstan practice has been carried out. Considering the Triple Helix concept of innovation development, a proposal is made to introduce a fourth player – the civil society, which ensures the influence and voice of the people and serves as a channel of communication with the authorities. The solution of the innovation problem presented in the article is of interest to the post-Soviet countries and emerging economies, where social issues and the welfare of citizens have not received sufficient attention, but the components of the Triple Helix (government, universities and business) do not work without their solution. The distinction of the study lies in the development of a model of the fourth helix of innovation development, which reflects the state of the civil society and socioeconomic processes in the country.